Sleeping upside-down: Knockdown of a sleep-associated gene induces daytime sleep in the jellyfish Cassiopea - Michael J. Abrams; Aki Ohdera; Diana A. Francis; Owen Donayre; Henry Chen; Kevin Lu; Celeste Y. Hsu; Hannah Zeigler; Richard M. Harland (Proceedings of the National Academy of Sciences, 2025)
The conservation of sleep among diverse animals provides clear evidence for its physiological importance, but the extent of its regulatory conservation is unknown. The upside-down jellyfish Cassiopea xamachana sleeps, and this behavior is controlled by radially spaced marginal ganglia. After defining a sleep–wake threshold, we compared gene expression profiles of ganglia from animals deprived of sleep and found differential expression in many sleep-related genes including GABAergic, melatonergic, and cholinergic receptors. In particular, a nicotinic acetylcholine receptor alpha subunit-like (Chrnal-E) was strongly differentially expressed in sleep deprived animals. Animals deprived of sleep under both mechanical and light perturbations suggested chrnal-E as a key gene regulating sleep. We found that chemical cholinergic neuromodulators regulate pacemaker activity. Visualization of chrnal-E mRNA revealed it is expressed primarily within the ganglia, and that the area of expression expands after sleep deprivation. In order to confirm the functional role of chrnal-E , we developed RNAi for use in Cassiopea and determined that Chrnal-E promotes wakefulness. Finally, we field-sampled control and sleep deprived animals and found chrnal-E has lowest expression late at night in controls, while in sleep deprived animals, chrnal-E peaks at this time, supporting a link to wakefulness. Our finding that Cassiopea sleep is regulated by the cholinergic-like system underscores that some components of sleep regulation are deeply conserved even in an animal with a distributed nervous system.